Targeted approaches in the treatment of osteoporosis: differential mechanism of action of denosumab and clinical utility - Cavalli L; Brandi ML (Dove Medical Press, 2012)
Loredana Cavalli, Maria Luisa BrandiUnit of Mineral and Bone Metabolism Diseases, Department of Internal Medicine, Traumatologic Orthopedic Center, Florence, ItalyAbstract: Denosumab is a breakthrough biological drug approved by the Food and Drug Administration and European Medicines Agency for the treatment of osteoporosis in 2010. It is a fully human monoclonal antireceptor activator of nuclear factor kappa-B ligand antibody, which inhibits the activity of osteoclasts, resulting in an antiresorptive effect with a significant increase in bone mineral density. The FREEDOM (Fracture Reduction Evaluation of Denosumab in Osteoporosis every 6 Months) trial, comparing denosumab with no treatment in 7868 women with postmenopausal osteoporosis, showed an important reduction of fracture risk at hip, vertebral, and nonvertebral sites in the treated group, while no statistically significant difference in the incidence of adverse events was detected between denosumab and placebo groups. The specific action of denosumab directed against a key regulator of osteoclasts makes it a valuable tool in preventing the occurrence of skeletal events caused by bone destruction in patients with advanced malignancies. The drug was approved for postmenopausal osteoporosis in women at increased risk of fracture and for the treatment of bone loss associated with androgen deprivation therapy in men with prostate cancer.Keywords: osteoporosis, denosumab, targeted therapy, BMD, antibody, RANK-L